PDRN prevents SIRT1 degradation by attenuating autophagy during skin aging - Jingjing Chen; Fanshan Qiu; Jianfeng Shi; Wei Huang; Chenyu Zhao; Qianqian Han (PLoS ONE, 2025)
Polydeoxyribonucleotide (PDRN) is a low molecular weight linear polyribonucleotide fragment derived from salmon sperm, known for its potential in tissue regeneration and anti-inflammatory applications. However, its specific function in cellular senescence is yet to be fully understood. Silent information regulator 1 (SIRT1), an NAD + -dependent deacetylase, plays a crucial role in regulating cellular aging and tumorigenesis. Notably, SIRT1 levels decrease with age in both mice and during cellular senescence, highlighting its significance in anti-aging processes. This study assessed the effects of PDRN on cellular aging induced by ultraviolet B (UVB) or hydrogen peroxide (H2O2) and investigated the mechanisms of its protective effects against aging at the cellular level. Our data demonstrated that PDRN treatment mitigated the decline in cell viability and inhibited cell aging when exposed to UVB or H2O2. Furthermore, PDRN ameliorated UVB-induced epidermal thickening in mouse skin. Mechanically, we found that PDRN treatment led to a reduction in nuclear autophagy and the formation of cytoplasmic stress granules by preventing the accumulation of damaged LC3 in the nuclear and inhibiting the degradation of SIRT1 and p62 in the cytoplasm during cellular senescence. In conclusion, PDRN exhibits antioxidant and anti-aging properties by diminishing autophagy and enhancing SIRT1 expression. These results suggest that PDRN has potential as a therapeutic compound for reducing skin aging induced by UVB or H2O2 through the modulation of SIRT1 levels.